Relayout Tata Letak Ruang Produksi untuk Meminimalkan Biaya Material Handling pada PT Pireki Asia - Wardani, Ni Kadek Ayu; Herlina, Herlina (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study was conducted at PT Pireki Asia, a manufacturing company producing partition doors, which has experienced inefficiencies in its production layout due to increasing demand and irregular material flow. The purpose of this research is to redesign the production facility layout to minimize material travel distance and time, and to reduce material handling costs. This original research was carried out through direct observation, measurement of interdepartmental distances, and analysis of activity relationships using the Systematic Layout Planning (SLP) method, including the development of a From-To Chart, Activity Relationship Chart, and space requirement evaluation. The findings show that the proposed layout significantly reduces material movement distance, improves process flow, and lowers material handling costs compared to the existing layout. The study recommends implementing the redesigned layout to enhance operational efficiency and support higher production capacity.